Stroke Volume Recruitability during the Third Trimester of Pregnancy - Herrera, Sandra; Kuhlmann-Capek, Maggie J.; Rogan, Sarah C.; Saad, Antonio F.; Saade, George R.; Hankins, Gary D. V.; Pacheco, Luis D. (American Journal of Perinatology, 2018)
Objective It is unknown whether the heart operates in the ascending or flat portion of the Starling curve during normal pregnancy. Pregnant women do not respond to the passive leg-raising maneuver secondary to mechanical obstruction of the inferior vena cava by the gravid uterus. Our objective was to evaluate if administration of a fluid bolus increases baseline stroke volume (SV) among healthy pregnant patients during the third trimester.Study Design Healthy pregnant women who underwent elective term cesarean sections were included. A noninvasive cardiac output monitor was used to measure hemodynamic variables at baseline and after administration of a 500-mL crystalloid bolus.Results Forty-five women were included in the study. Fluid administration was associated with a statistically significant increase in SV from a baseline value of 71 ± 11 to 90 ± 19 mL (95% confidence interval [CI]: 13.67–21.49; p < 0.01) and a significant decrease in maternal heart rate from a baseline of 87 ± 9 beats per minute to 83 ± 8 after the fluid bolus (95% CI: −6.81 to −2.78; p = 0.03). No changes in peripheral vascular resistances or any other measured hemodynamic parameters were noted with volume expansion.Conclusion In healthy term pregnancy, the heart operates in the ascending portion of the Starling's curve, rendering it fluid responsive.
Keywords: stroke volume; cardiac output; late pregnancy; passive leg raising; fluid bolus